2016
DOI: 10.1080/0886022x.2016.1227617
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mutant lactobacilli on serum creatinine and urea nitrogen concentrations and renal pathology in 5/6 nephrectomized rats

Abstract: Objectives: To explore the capacity of mutant lactobacilli to remove creatinine (Cr) and urea nitrogen (UN) via the gastrointestinal tract and its effects on renal pathology in the 5/6 nephrectomized rat model of chronic renal failure. Methods: Sixty Sprague-Dawley rats were randomly divided into a Sham group, a Model group, a wide-type Lactobacilli group (L.B group), and a Mutant Lactobacilli group (Mut-L.B group). The rats in the Model, LB and Mut-L.B groups underwent 5/6 nephrectomy. Eight weeks after admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Comparison of biochemical parameters among the mice in the PTX-SLN@CUD acute toxicity group compared to the control group showed that one mouse had an LDH value that was slightly below the reference range, while the CREA index of another mouse was slightly lower than the reference range without any clinical guiding significance (Table 5). 46 In general, only one or two biochemical indexes were abnormal in the same group of mice, which confirmed the negligible liver and kidney injury of mice by PTX-SLN@CUD. In the cumulative toxicity assay, the relevant indicators of each mouse in the PTX group revealed that there were high values compared to the control group.…”
Section: Blood Biochemical Parametersmentioning
confidence: 60%
“…Comparison of biochemical parameters among the mice in the PTX-SLN@CUD acute toxicity group compared to the control group showed that one mouse had an LDH value that was slightly below the reference range, while the CREA index of another mouse was slightly lower than the reference range without any clinical guiding significance (Table 5). 46 In general, only one or two biochemical indexes were abnormal in the same group of mice, which confirmed the negligible liver and kidney injury of mice by PTX-SLN@CUD. In the cumulative toxicity assay, the relevant indicators of each mouse in the PTX group revealed that there were high values compared to the control group.…”
Section: Blood Biochemical Parametersmentioning
confidence: 60%
“…Blood urea nitrogen (BUN) and serum creatinine (Cr) are two essential indicators widely used in the assessment and evaluation of renal functions independently (Akimoto et al, ; Chen, ; Naqshbandi, Khan, Rizwan, Rehman, & Khan, ). In fact, previous studies have shown that serum Cr and BUN were downregulated in the presence of a corosolic acid or the mutated lactobacilli (Li et al, ; Wang, Jiang, & Liu, ). Recently, many researchers have also noted that serum Cr and BUN levels were markedly increased after some renal‐related treatments, such as the cisplatin treatment, and the renal Ischemia/reperfusion treatment (Domitrovic et al, ; Saigo et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Comparison of biochemical parameters of mice in the CUD-PTX-LN acute toxicity group with that of the control group, only one mouse had an LDH value slightly below the reference range. In addition, the CREA index of another mouse is slightly lower than the reference range but has no clinical guiding signi cance (Table 2) [41]. In general, only one or two biochemical indexes were abnormal in the same group of mice, con rming to some extent that liver and kidney injury brought by CUD-PTX-LN to mice was limited.…”
Section: Blood Biochemical Parametersmentioning
confidence: 93%